Design of Concept Art and 2D Frame by Frame Animation in the Animation 'Spectrum Rise’ - Antris, Ardhia Gagas Dhaifullah; Sheanny Ocmi Sakti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This project addresses the issue of low literacy rates in Indonesia, highlighting the need for creative approaches to foster reading interest. An animation titled